2010
DOI: 10.2165/11530160-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Adverse Effects of Ketoprofen for Topical Use

Abstract: Topical ketoprofen is used to treat benign symptoms but can be associated with serious and costly cutaneous ADRs. Furthermore, the number of cases and the calculated costs may have been greatly under-estimated in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
(12 reference statements)
0
13
0
1
Order By: Relevance
“…The costs of skin ADEs related to antineoplastic agents were estimated from €1,592.89 to €15,037.97 36,37. A study evaluated the costs of nonserious and serious skin ADEs according to spontaneous reports; the incremental total cost per patient was estimated as €373.33 and €3,383.56, respectively 38. Suh et al estimated the costs of levodopa-induced dyskinesia as €4,617.65 39.…”
Section: Resultsmentioning
confidence: 99%
“…The costs of skin ADEs related to antineoplastic agents were estimated from €1,592.89 to €15,037.97 36,37. A study evaluated the costs of nonserious and serious skin ADEs according to spontaneous reports; the incremental total cost per patient was estimated as €373.33 and €3,383.56, respectively 38. Suh et al estimated the costs of levodopa-induced dyskinesia as €4,617.65 39.…”
Section: Resultsmentioning
confidence: 99%
“…PACD is considered as an uncommon or rare condition, and limited data are available concerning incidence. In Italy, the observed rate of any reported photosensitivity reaction to drugs (including photoallergy and phototoxicity from topical and systemic agents) was 1.86 per million inhabitants per year (corresponding to 5.5 per 100 000 adverse reactions reported) . Similarly, in Norway, a retrospective analysis of adverse drug reaction reports for the years 1970–1995 revealed that approximately 5 per 100 000 reactions were classified as photosensitivity …”
Section: Introductionmentioning
confidence: 99%
“…; Noize et al. ). To date, however, there is limited information on the incidence of severe photosensitivity reactions leading to hospitalization among topical ketoprofen users as compared with users of other topical NSAIDs.…”
Section: Introductionmentioning
confidence: 97%
“…; Noize et al. ). In an analysis of spontaneous reports in Italy, the observed reporting rate of photosensitivity reactions from any causes was 5.5 per 100,000 inhabitants per year and the rate of serious photosensitivity reactions was 0.09 per 100,000 inhabitants per year (Naldi et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation